Incorporating HIV/hepatitis B virus/hepatitis C virus combined testing into routine blood tests in nine UK Emergency Departments: the "Going Viral" campaign. Issue 3 (March 2016) - Orkin, C; Flanagan, S; Wallis, E; Ireland, G; Dhairyawan, R; Fox, J; Nandwani, R; O'Connell, R; Lascar, M; Bulman, J; Reeves, I; Palfreeman, A; et al.
Abstract : Objectives: Routine HIV screening is recommended in those UK hospitals and primary care settings where the HIV prevalence is > 0.2%. For hepatitis B virus (HBV) and hepatitis C virus (HCV), however, testing is targeted at at‐risk groups. We investigated the prevalence of these blood‐borne viruses (BBVs) during a routine testing pilot in UK Emergency Departments (EDs). Methods: During the "Going Viral" campaign (13–19 October 2014), nine UK EDs in areas of high HIV prevalence offered routine tests for HIV, HBV and HCV to adults having blood taken as part of routine care. Patients who tested positive were linked to care. Results: A total of 7807 patients had blood taken during their ED visit; of these, 2118 (27%) were tested for BBVs (range 9–65%). Seventy‐one BBV tests were positive (3.4%) with 32 (45.1%) new diagnoses. There were 39 HCV infections (15 newly diagnosed), 17 HIV infections (six newly diagnosed), and 15 HBV infections (11 newly diagnosed). Those aged 25–54 years had the highest prevalence: 2.46% for HCV, 1.36% for HIV and 1.09% for HBV. Assuming the cost per diagnosis is £7, the cost per new case detected would be £988 for HCV, £1351 for HBV and £2478 for HIV. Conclusions: In the first study in the UK to report prospectively on BBV prevalence in the ED, we identified a high number of new viral hepatitis diagnoses, especially hepatitis C, in addition to the HIV diagnoses. Testing for HIV alone would have missed 54 viral hepatitis diagnoses (26 new), supporting further evaluation of routine BBV testing in UK EDs.